Maggie, too - Nixon, Joan Lowery (San Diego : Harcourt Brace Jovanovich, 1985)
A defensive twelve-year-old comes to understand her father, a busy Hollywood director planning to remarry, after she is exiled for the summer to the everyday life of her grandmother's house in Houston.
Accelerated Reader AR
Keywords: Children's stories, American; Fathers and daughters -- Fiction; Grandmothers -- Fiction; Family life -- Fiction